Design of low-orbit small spacecraft with optical surveillance equipment and corrective electric propulsion system - Yе. V. Shakhmatov; V. V. Salmin; V. V. Volotsuev (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
The project of a low-orbit optical remote sensing spacecraft with a corrective electric propulsion system is described. The target equipment includes optical equipment formed according to the Ritchie-Chretien scheme with an additional re-reflection mirror. The choice of the geometry of optical equipment is justified by reducing the area of the spacecraft's midsection (to reduce the drag force from the upper atmosphere of the Earth). The guideline is the possibility of creating a small spacecraft (weighing no more than 1000 kg) to obtain satellite images with high spatial resolution (the pixel projection size on the Earth is less than 30 cm). The article presents a model of limitations from the satellite's power supply system on the operating modes of an electric propulsion system and the results of an analysis to estimate the parameters of the orbit correction cycles and the mass of the working fluid reserves.